2020
DOI: 10.1111/jeb.13617
|View full text |Cite
|
Sign up to set email alerts
|

The combined effect of host and food availability on optimized parasitoid life‐history traits based on a three‐dimensional trade‐off surface

Abstract: The reproductive success of many insects is considered to be limited by two main factors: the availability of mature eggs to lay (termed egg limitation) and the time to locate suitable hosts (termed time limitation). High host density in the environment is likely to enhance oviposition opportunities, thereby selecting for higher investment in egg supply. In contrast, a shortage of food (e.g. sugar sources) is likely to increase the risk of time limitation, thereby selecting for higher allocation to initial ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 70 publications
1
7
0
Order By: Relevance
“…4 ). This lower fecundity is expected if there is an egg number-egg size trade-off, as higher competition in core patches would favour larger, more competitive larvae (Segoli & Wajnberg, 2020). For instance, in Callosobruchus chinensis beetles parasitising seeds, higher larval competition within seeds leads to adults producing both a reduced number of eggs (Vamosi, 2005) and larger eggs [after accounting for emerging female size; Yanagi et al (2013)].…”
Section: Discussionmentioning
confidence: 99%
“…4 ). This lower fecundity is expected if there is an egg number-egg size trade-off, as higher competition in core patches would favour larger, more competitive larvae (Segoli & Wajnberg, 2020). For instance, in Callosobruchus chinensis beetles parasitising seeds, higher larval competition within seeds leads to adults producing both a reduced number of eggs (Vamosi, 2005) and larger eggs [after accounting for emerging female size; Yanagi et al (2013)].…”
Section: Discussionmentioning
confidence: 99%
“…For example, high fecundity is often considered desirable as it may allow agents to attack many pest individuals and to experience rapid population growth. However, investment in fecundity can come at the expense of other traits such as longevity, egg size and dispersal ability [26][27][28] all of which may influence success. Moreover, the allocation of resources between fecundity and other traits may be highly dependent on environmental conditions (see also 'Variable environmental contexts' below).…”
Section: Limited Information On Traitsmentioning
confidence: 99%
“…Against this backdrop of debates, theoretical work has coalesced on the prediction that natural selection will favor traits that balance multiple limiting factors, such that different factors limit fitness at different times or places (Dawkins, 1995 ; Haig & Westoby, 1988 ). But not all factors are predicted to have equal likelihoods of limiting fitness; rather, balanced limitations theory predicts that it is the physiological cost of alleviating the impact of a particular limiting factor that shapes the likelihood of that factor emerging as the limit to fitness (Ellers et al., 2000 ; Rosenheim, 2011 ; Rosenheim et al., 2010 ; Segoli & Wajnberg, 2020 ). The more expensive it is to harvest a particular resource, the more likely a shortfall of that resource is predicted to limit reproductive success.…”
Section: Introductionmentioning
confidence: 99%
“…One exception has come from a new study of egg limitation in insect parasitoid wasps: Segoli et al. ( in press ) demonstrated that egg costs (measured as the size of an egg relative to the size of the female parasitoid) are positively correlated with the likelihood that a female parasitoid's lifetime reproductive success would be limited by the female's finite supply of eggs. In most cases, however, measuring realized lifetime reproductive success in nature is difficult, and determining what factor limits reproductive success for a given individual or across a population is even more difficult.…”
Section: Introductionmentioning
confidence: 99%